A review of design factors in steam and gas push for eco-friendly oil sands production and its field application in Canada - Sunghyun Kim; Hyundon Shin; Changhyup Park; Zhuoheng Chen; Kyungbook Lee (Journal of Petroleum Exploration and Production Technology)
Abstract Steam and gas push (SAGP) reduces greenhouse gas emissions by co-injecting non-condensable gas (NCG) with steam, preventing heat loss to thief zones and maintaining steam chamber pressure and temperature. However, NCG can hinder steam chamber growth, reducing oil production than steam-assisted gravity drainage (SAGD). Additionally, determining the type, concentration, and injection timing of NCG based on the given reservoir conditions can be challenging. Nitrogen and methane are commonly used NCGs due to their low solubility in oil, but concentrations above 3 mol% typically decreases SAGP efficiency. To prevent NCG interference with steam chamber, an injection pressure of 0.95–1.1 times reservoir pressure and an NCG injection between 0 and 0.6 times total production period are recommended. Numerical simulations showed that injecting NCG after 0.125, 0.25, and 0.375 times total 8-year production period increased cumulative oil production by 18.6%, 163.7%, and 218.6% respectively, compared to injection from the start. Sensitivity ranges for reservoir parameters include thief zone thickness of aquifer (0–0.5 times reservoir thickness), ratio of vertical to horizontal permeability for sandstone (0.3–0.65), and oil viscosity based on major oil sands regions in Canada (2,000,000 cp. for Athabasca, 200,000 cp. for Peace River, and 60,000 cp. for Cold Lake at 12 °C). Thicker thief zones increase heat loss and higher vertical permeability accelerates steam chamber rise, requiring earlier NCG injection. Additionally, lower oil viscosity regions are more suitable for SAGP. Field application of Suncor Firebag project that NCG reduced cumulative steam-oil ratio from 3.14 to 2.76, demonstrating SAGP’s effectiveness.